Bulbostylis maritima—A new species of Cyperaceae from coastal Kerala, India - Sunil, Chandrasseril Narayanan; Prasad, Vadhyaruparambil Prabhakaran; Kumar, Vannaratta Naveen (Phytotaxa, 2020)
Bulbostylis maritima (Cyperaceae) is described as a new species along with colour photograph, illustration and SEM micrographs of achene surface. It is closely allied to B. subspinescens  and B. barbata, but differs by a combination of characters, mainly by the densely tubercled achenes, presence of prominent cavities on the rachilla, prominently ciliate bracteoles at the base of spikelets and a knee-like swelling towards base of the glumes.